Zinc Oxide Nanoparticles: A Review on Its Applications in Dentistry - Pushpalatha, C; Suresh, Jithya; Gayathri, VS; Sowmya, SV; Augustine, Dominic; Alamoudi, Ahmed; Zidane, Bassam; Mohammad Albar, Nassreen Hassan; Patil, Shankargouda (Frontiers in Bioengineering and Biotechnology, 2022)
Nanotechnology in modern material science is a research hot spot due to its ability to provide novel applications in the field of dentistry. Zinc Oxide Nanoparticles (ZnO NPs) are a metal oxide nanoparticle that open new opportunities for biomedical applications that range from diagnosis to treatment. The domains of these nanoparticles are wide and diverse and include the effects brought about due to the anti-microbial, regenerative, and mechanical properties. The applications include enhancing the anti-bacterial properties of existing restorative materials, as an anti-sensitivity agent in toothpastes, as an anti-microbial and anti-fungal agent against pathogenic oral microflora, as a dental implant coating, to improve the anti-fungal effect of denture bases in rehabilitative dentistry, remineralizing cervical dentinal lesions, increasing the stability of local drug delivery agents and others.